Modified high frequency probe approach for diagnostics of highly reactive plasma. (13th November 2019) - Sezemsky, Petr; Stranak, Vitezslav; Kratochvil, Jiri; Cada, Martin; Hippler, Rainer; Hrabovsky, Miroslav; Hubicka, Zdenek
Abstract: The paper introduces a modified approach of time resolved in situ diagnostics of highly reactive discharges (C2 H2 in our case) usually used for a deposition process of various non-conductive thin films. Reactive plasma could create an insulating film onto inserted diagnostic tools, which distorts measured data and makes their processing unreliable; a typical problem of Langmuir probe measurements. The proposed approach utilizes a so-called radiofrequency (rf) Sobolewski probe for ion flux measurement which is further modified to also obtain the electron temperature in some cases and the ion density. In this work, we introduce the procedure where measured rf probe characteristics are transformed towards I – V curves of the plasma sheath with subtracted capacitive current. This processing enables not only the monitoring of plasma sheath impedance and the ion flux towards the substrate but also allows for an estimation of other parameters as the plasma density or electron temperature, respectively. We demonstrate that the substrate used for thin film deposition can act as an active probe itself. The relevance of the proposed method was verified in pure Ar discharge where the results correspond with conventional Langmuir probe diagnostics. Furthermore, internal plasma parameters of highly reactive Ar/C2 H2 plasma, formed from acetylene, were evaluated, too.